Grit at Work The Role of Perceived Social Support on Grit in Government Employees by Age - Hawabi, Agus Iqbal; Muna, Robiatin Nailil Muna (Proceedings Conference Psychology and Flourishing Humanity; Vol 2 No 1 (2025): Proceedings Conference on Psychology and Flourishing Humanity, 2026)
In every organization, whether profit-oriented or not, humans are the primary resource that plays a crucial role in achieving organizational or institutional goals effectively and efficiently. In carrying out their duties and responsibilities, several employees at DP3AP2KB of Malang City and Malang Regency face similar problems and challenges related to workload, which affects their performance. This study aims to examine the effect of perceived social support on grit among government employees and to investigate whether age moderates this relationship. This research uses a quantitative approach with Moderated Regression Analysis (MRA) as the analytical technique. The study involved 107 employees from two government institutions in Malang City and Malang Regency, selected using proportionate stratified random sampling. The instruments used were the Grit Scale and the Multidimensional Scale of Perceived Social Support (MSPSS). The analysis results show that perceived social support has a positive and significant effect on grit (p = 0.001). However, age does not have a significant effect (p = 0.829) and does not moderate the relationship between perceived social support and grit (p = 0.178). Descriptively, employees over the age of 50 have the highest average levels of both grit and perceived social support compared to other age groups.